Ameliorative Effect of Eruca sativa Seeds and Its Rutin on Gentamicin‑Induced Nephrotoxicity in Male Rats via Targeting Inflammatory Status, Oxidative Stress and Kidney Injury Molecule-1 (KIM-1)/Cystatin C Expression - Reda Salah-Eldin Abdelkader; Nadia Mohamed El-Beih; Samir Attia Zaahkouk; Enas Ali El-Hussieny (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Nephrotoxicity of Gentamicin (GM), an important aminoglycoside, is still a serious issue in clinical use. Therefore, natural products are currently being used as an alternate source of medicinal substances by researchers all over the world for new medication molecules. Eruca sativa shows several health benefits that appear to be associated with the content of flavonoids. Therefore, the objective of the present study was to evaluate the effect of  E. sativa seed extract (ESE) and its active flavenol rutin (RUT) in GM-induced nephrotoxicity in adult male rats. METHODS: The animals were divided into 10 groups: a control group, a groups administered 150 mg/kg body weight (BW) of ESE, a group administered 300 mg/kg BW of ESE, a group administered with 50 mg/kg BW of RUT, a group administered with 100 mg/kg BW of RUT, a GM-nephrotoxic group, and four GM-nephrotoxic groups treated with the same doses of ESE and RUT as previous groups. The treatments were given orally for 4 weeks. Following the treatments animals in all groups were sacrificed. The blood samples were drawn, and the kidney tissue samples were collected for further analysis.RESULTS: ESE alleviated the nephrotoxic effects of GM as it decreased the serum levels of creatinine, urea, Na+, K+, tumor necrosis factor-α (TNF- α), and interleukin-1β (IL-1β). Moreover, ESE was linked with kidney injury molecule-1 (KIM-1) and Cystatin C mRNA downregulation. Although treatment with pure RUT induced the same modulation of ESE in GM- nephrotoxic rats, pure RUT was more effective than ESE in the modulation of oxidative kidney injury.CONCLUSION: The present study revealed the health-promoting effects of ESE or RUT in the attenuation of GM-induced nephrotoxicity.KEYWORDS: nephrotoxicity, gentamicin, Eruca sativa, rutin, inflammation, KIM-1/cystatin C expression